Hubungan Pemberian Asi Ekslusif Terhadap Involusi Uteri di Wilayah Kerja Puskesmas Telaga - Abdul Kadim Masaong; Sabirin B. Syukur; Devi Saraswati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Breastfeeding is one of the important roles for mothers and baby because apart from having great benefits for mothers and babies it also has the side effect of improving uterine involution. The Objective of research was to analyze the relationship between exclusive breastfeeding and uterine involution in Telaga Health Center. This research is a type of quantitative research with a cross sectional approach. The sampling technique used the total sampling technique. The statistical test results obtained the value of Chi-Square p = 0.038 with ? ? 0.05. the benefits of breastfeeding help mothers recover from the birth process. Breastfeeding during the first few days makes the uterus contract quickly and slows down bleeding (sucking on the nipples stimulates the release of natural oxytocin which will help uterine contractions). Breastfeeding is an important way for mothers to express love to their babies and make them feel comfortable. Thus, it can be concluded, there is a relationship between exclusive breastfeeding and uterine involution in the Telaga Health Center Work Area. It is expected the Telaga Health Center will provide data or information from this research to provide and improve the quality of services for pregnant/postpartum women in preventing uterine subinvolution.